8 mJ 355 nm 1 kHz burst-mode picosecond laser systems. (1st April 2022) - Wang, C L; Chen, M; Xiang, H P; Zhang, Z Y; Tao, R Q
Abstract: This paper presents an 8 mJ 355 nm 1 kHz burst-mode picosecond laser system, where the energy of each subpulse in the burst mode is 2 mJ. Under optimal operational conditions, a noncritical phase-matched LiB3 O5 (LBO) crystal and a type-II angle- and phase-matched LBO crystal are used as the second- and third-harmonic generation crystals, respectively. The largest conversion efficiency from 1064 nm to 355 nm was 38%, and the highest output power at 355 nm was 8 W; further, the beam quality was measured as M x 2 = 2.46 and M y 2 = 2.84 .